Past, present, and future of carbon accounting: Insights from scholarly research - Hazaea, Saddam A.; Al-Matari, Ebrahim Mohammed; Alosaimi, Mushari Hamdan; Farhan, Najib H. S.; Abubakar, Ahmed; Zhu, Jinyu (Frontiers in Energy Research, 2023)
Although accounting functions have expanded from traditional practices to recent practices focusing on environmental, social, and governance issues. However, there is a shortcoming in conceiving different approaches to creating organizational and human interaction with the environment. In this study, we review the existing research on carbon accounting from 1994 to July 2022 in order to examine its intellectual development and make recommendations for future studies. This study also discusses the scales, methodological choices, and major themes of carbon accounting research, including the most influential articles and top contributing countries, journals, theories, and institutions. The literature was retrieved from Web of Science (WoS) and Scopus databases, in which 137 articles were obtained from 62 high-quality journals in accounting, environment, and economics. There has been a significant increase in recent years in the number of studies, with the majority taking place in the United Kingdom, Australia, and China, as compared to the United States. On the other hand, the results show that traditional theories such as the theory of legitimacy, the theory of organization, and the theory of stakeholders, have been evaluated previously. Although a firm's characteristics and consumer behavior play an important role in improving carbon efficiency, economic and behavioral theories have been underrepresented in the existing literature. Furthermore, it is found that carbon accounting research provides a mechanism through which carbon emissions can be measured and quantified and helps in knowing the emissions status of companies and making the necessary strategic decisions to achieve mitigation. Therefore, policymakers have to foster setting international standards that would compile firms to report their carbon strategies similar to the international financial reporting standards, allowing investors to verify and compare firms that are performing well in terms of carbon reduction.